Global Financial Stability Report, October 2019 : Lower for Longer. (Global Financial Stability Report; Global Financial Stability Report ;, 2019)
The October 2019 Global Financial Stability Report (GFSR) identifies the current key vulnerabilities in the global financial system as the rise in corporate debt burdens, increasing holdings of riskier and more illiquid assets by institutional investors, and growing reliance on external borrowing by emerging and frontier market economies. The report proposes that policymakers mitigate these risks through stricter supervisory and macroprudential oversight of firms, strengthened oversight and disclosure for institutional investors, and the implementation of prudent sovereign debt management practices and frameworks for emerging and frontier market economies.